2014
DOI: 10.4236/msce.2014.21003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pressure on the Synthesis of Graphene Layers in the Flame

Abstract: The results of the study of the formation of graphene layers in the flame in premixed flame propane or butane-oxygen mixture on a nickel substrate at atmospheric pressure and low pressure are given. The influence of the ratio C/O and supply quantity of argon on the formation of graphene layers were researched. It is shown that in the flame of propane and butane on a nickel substrate is observed under these conditions the formation of predominantly 3-10 layers of graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
2
4
0
Order By: Relevance
“…The shift to a lower 2D wave number indicated a decrease in the number of layers. [81][82][83] These results are in line with the particle sizes of the GF tt and GnP tt obtained by I D /I G mapping (Figure 3b) and SEM imaging (Figure 2d,e).…”
Section: Hybrid Gf Tt -Gnp Tt Compositesupporting
confidence: 88%
See 1 more Smart Citation
“…The shift to a lower 2D wave number indicated a decrease in the number of layers. [81][82][83] These results are in line with the particle sizes of the GF tt and GnP tt obtained by I D /I G mapping (Figure 3b) and SEM imaging (Figure 2d,e).…”
Section: Hybrid Gf Tt -Gnp Tt Compositesupporting
confidence: 88%
“…The observed Raman spectrum agrees with previously reported data. [80][81][82][83] The I D /I G mapping (Figure 3b) indicated the coexistence of large GF tt particles (≈50 μm in size, Figure 2d), with a low edge defect density, and exfoliated small GnP tt particles (≈10 μm in size, Figure 2e), with a higher edge defect density, [84,85] in agreement with the SEM results (Figure 2c). As expected, the relatively smaller GnP tt particles had a higher edge concentration than the GF tt particles and, consequently, a higher I D /I G ratio.…”
Section: Hybrid Gf Tt -Gnp Tt Compositesupporting
confidence: 84%
“…Investigations on synthesis of graphene layers in hydrocarbon flame at low pressure have shown that the formation of graphene layers is occurred in sooting zone as well as at atmospheric pressure, as was shown in [22][23][24]. Figure 3 shows the Raman spectra (a) that characterizing the carbon structures are formed on nickel plate in areas 0, 1, 2, 3 (b).…”
Section: Formation Of a Layered Graphene Films In Flamesmentioning
confidence: 87%
“…The Raman-spectra of carbon structures in accordance with (a) zones; and photo of nickel substrate (b) with an indication of formed carbon structure zones (P = 90 Torr, C/O = 0.8, T = 900 °C, t = 30 sec)[23].…”
mentioning
confidence: 95%
“…The studies confirm that the process of achieving a flame graphene cannot compete with other existing methods. The process of formation of graphene in a flame is continuous, rapid, and cheap technique [6] . Flame synthesis is a high-temperature synthesis technique, which includes only a single-step process, resulting in a large-scale approach for fabricating diverse materials involving low-dimension carbon structures such as CNTs, fullerenes, and amorphous carbon thin films [7] .…”
Section: Introductionmentioning
confidence: 99%